Effect of beams structures on dynamic behavior of piezoresistive accelerometer sensors - Yusof, N.; Soin, N.; Noorakma, A.C.W. (Universiti Teknikal Malaysia Melaka, 2017)
This paper presents the design and simulation analysis of MEMS piezoresistive accelerometer sensor which can be used as airbag sensors. In this study, five different shapes of accelerometer structures with identical proof mass volume are designed and simulated by using Comsol Multiphysics software. The static analysis and modal analysis were conducted to investigate the stress, displacement, strain and resonant frequency of each structure. From the static analysis, it can be observed that structure with four beams parallel to the proof mass and attached at the edge of it, perform the highest value of stress, 6.78 X108 N/m2. In this study, the minimum natural frequency of 2 kHz is chosen as a hard constraint in order to obtain a bandwidth at least of 400 Hz to meet requirements for airbag application. From the modal analysis, the structure with four beams connected in the middle of each of the four sides of the proof mass and the structure with eight beams surrounding the proof mass has demonstrated more than the acceptable natural frequency with 6.79 kHz and 2.00 kHz respectively. From this study, it has been shown that the structure with a proof mass surrounded by eight beams is the best choice for achieving maximum mechanical sensitivity and desirable resonant frequency for airbag sensor applications.